THE EFFECT OF GIVING SNAKEHEAD FISH SUPPLEMENTATION THERAPY (STRIATED CHANNA) ON BODY WEIGHT IN TUBERCULOSIS PATIENTS AT THE SIDOTOPO HEALTH CENTER IN SURABAYA - Alfia Andriyani; Jusak Nugraha; Retno Indrawati; Theresia Indah Budhy (Universitas Airlangga, 2023)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. This study aims to determine the effect of supplementing snakehead fish (Channa striata) on body weight at the Sidotopo Health Center. The method used in this study was a one group pre test post test design involving 20 patients using a purposive sampling. The study inclusion criteria were clients who had just been diagnosed with active tuberculosis, took OAT regularly, aged 18-60 years. Exclusion criteria were TB patients who refused the study, MDR (Multi drug Resistance) TB, smokers, had a history of allergies, took other supplements. This research was conducted in June 2022 at the Sidotopo Health Center in Surabaya. Laboratory analysis was carried out at the Tropical Disease Institute, Airlangga University. The results of statistical tests in this study were that there were differences in the administration of snakehead fish (Channa striata) on body weight in tuberculosis patients with a p-value = 0.000 (<0.005). The pretest reached 46.25 kg, while the post test body weight was 48.20 kg. This shows that there is an increase in body weight in TB patients at the Sidotopo Health Center in Surabaya. Keywords : Weight, Tuberculosis, Snakehead fish